Programming Language Pragmatics - Scott, Michael; Scott, Michael (Morgan Kaufmann, 2015)
Programming Language Pragmatics, Fourth Edition, is the most comprehensive programming language textbook available today. It is distinguished and acclaimed for its integrated treatment of language design and implementation, with an emphasis on the fundamental tradeoffs that continue to drive software development.The book provides readers with a solid foundation in the syntax, semantics, and pragmatics of the full range of programming languages, from traditional languages like C to the latest in functional, scripting, and object-oriented programming. This fourth edition has been heavily revised throughout, with expanded coverage of type systems and functional programming, a unified treatment of polymorphism, highlights of the newest language standards, and examples featuring the ARM and x86 64-bit architectures. - Updated coverage of the latest developments in programming language design, including C & C++11, Java 8, C# 5, Scala, Go, Swift, Python 3, and HTML 5 - Updated treatment of functional programming, with extensive coverage of OCaml - New chapters devoted to type systems and composite types - Unified and updated treatment of polymorphism in all its forms - New examples featuring the ARM and x86 64-bit architectures